The Phenomenon of Fear of Missing Out (FOMO) and Its Impact on the Personal Financial Accounting Of Generation Z at Palu City Hall Ramadan Market - Alviani Ariska; Rasmi Nur Anggraeni; Farhan Nur; Rajindra Rajindra (Media Ilmiah Akuntansi, 2025)
This study aims to deeply understand the subjective experiences of Generation Z regarding Fear of Missing Out (FOMO) and its impact on personal financial accounting behavior at the Palu City Hall Ramadan Market. The Ramadan Market in the yard of the Palu Mayor’s Office in 2026 involved 192 local MSMEs and presented digital payment innovations through QRIS facilitated by Bank Indonesia. The phenomenon of increasing consumption transactions during the month of Ramadan triggered by visit trends on social media has the potential to disrupt personal financial accounting systems, especially for Generation Z with limited income. The study used a qualitative approach with a case study design. Data were collected through in-depth interviews with 12 Generation Z informants, participant observation, and documentation studies. Data analysis used the interactive model of Miles, Huberman, and Saldaña (2014). The results revealed six main themes: (1) FOMO causes weaknesses in personal financial recording; (2) FOMO triggers significant budget deviations; (3) the FOMO mechanism creates gaps in internal financial control; (4) accounting literacy acts as a protective factor; (5) the ease of digital payments weakens the audit trail and complicates reconciliation; and (6) there is a conflict between spiritual values and financial accountability. This research contributes to the development of personal financial accounting in the context of digital generation behavior.